1958
DOI: 10.2134/agronj1958.00021962005000100017x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Rotary Hoe for Weed Control in Soybeans1

Abstract: Synopsis Rotary hoeing performed when weeds were germinating but not emerged, and repeated once or twice at approximately 5‐day intervals, reduced weed infestations 70 to 80% and soybean stands about 10% in solid‐seeded and row‐planted soybeans. Bean yields were only slightly less than those from weed‐free plantings. When hoeing was delayed until weeds had emerged, both weed control and bean yield were impaired 50%. Wet soil conditions before or after hoeing reduced its effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
2

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 2 publications
0
39
2
Order By: Relevance
“…Organic production requires a complex management system. Various weed control methods can be used including mechanical cultivation (3,6,7); flame weeding and crop rotations (4); companion crops (9); cover crops (1,5,11); and other cultural, mechanical, and biological methods. However, replicated research on mechanical weed control effectiveness in certified organic production systems is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Organic production requires a complex management system. Various weed control methods can be used including mechanical cultivation (3,6,7); flame weeding and crop rotations (4); companion crops (9); cover crops (1,5,11); and other cultural, mechanical, and biological methods. However, replicated research on mechanical weed control effectiveness in certified organic production systems is limited.…”
Section: Introductionmentioning
confidence: 99%
“…The rotary hoe has long been known as an effective weed management tool . Multiple rotary hoeing alone and when combined with flame cultivation was reported to be effective for weed management in organic vegetable production .…”
Section: Adoption Of Selected Iwm Strategies To Manage Hr Weedsmentioning
confidence: 99%
“…Some investigations have shown that mechanical control costs about the same as herbicidal weed control, for corn and other crops (F.W. Slife, University of Illinois, personal communication, 1972;Lovely et al, 1958;Drew and van Arsdall, 1966;Armstrong et al, 1968;Buchholtz and Doersch, 1968;Mo1berg and Hay, 1968;Spurgeon and Cooke, 1971;Cooke, 1975). In general, however, mechanical and cultural weed controls cost more than herbicidal controls.…”
Section: Asparagus 112mentioning
confidence: 99%